The Impact of Dividend Policy on Shareholders' Wealth Based on Agency Cost and Residual Dividend Theory - Siad, Ahmed Abubakar Ahmed (2010)
This study attempts to shed light on dividend policy for Malaysian companies by seeking to understand the explanations for corporate dividend policy's effect on shareholder's wealth (Market Price Share), for the year 2007 to 2009, with the focus on Agency Cost Theory and Residual Theory. Three variables associated with Residual Theory namely Size, Growth opportunity (GO) and Capital expenditure (CAPEX) and two variables associated with Agency Cost Theory, namely Leverage (LEV) and Free cashflow (FCF) are the focus of the study where their interaction effect with Dividend Per Share (DPS) are hypothesised to have significant effect on share price. Earnings per share (EPS), Exachange rate (EXR) and Inflation (INF) are used as control variables. Results show that the interaction variables between DPS and CAPEX, DPS and Growth Opportunity have significant influence on share price but in the direction opposite to that hypothesized under Residual Dividend Policy. Nevertheless, the interaction effect between DPS and Size is also significant in influencing share price in the manner predicted by Residual Dividend Policy. Variable associated with agency Cost Dividend Theory are shown not to play a significant mediating role in the relationship between stock price and DPS.